A simple triangular plate bending element for the analysis of laminated anisotropic composite plates - De Wet, P. R.(Philippus Rudolf) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing.) -- University of Stellenbosch, 1987.